Analisis Pengaruh Dimensi Fraud Triangle Dalam Kebijakan Pencegahan Fraud Terhadap Program Jaminan Kesehatan Nasional di RSUP Nasional Cipto Mangunkusumo - Sadikin, Hasan; Adisasmito, Wiku (UI Scholars Hub, 2016)
The National Health Insurance (JKN) held by the Social Security Agency (BPJS) Health started to be implemented from 1 Indonesia’s Health Insurance Program in January 2014. The implementation of a national insurance program found the risk. The risk of occurrence of fraud in Indonesia is very high but it is still difficult to identify its risk. This is supported by the lack of awareness of all parties, including patients, providers and insurance companies although such actions exists. Health fraud is a serious threat to the entire world, which led to financial abuse of scarce resources and the negative impact on access to health care, infrastructure, and social determinants of health. Health fraud is associated with increased health care costs in the United States. This study was to analyze the influence of the dimensions of the fraud triangle in fraud prevention policies towards the National Health Insurance program which is the reason for health fraud. This study used a qualitative approach. Data collection techniques such as interview guides, recorders, written records and documents. The study reported stress analysis, opportunity, and rationalization of the risk of fraud incident and presents examples of how policy has an impact on the National Hospital Dr. Cipto Mangunkusumo. This thesis will then provide advice on how to prevent future fraudulent health to reduce health spending and use of resources for the benefit of the National Hospital Dr. Cipto Mangunkusumo.